Permaculture demonstration sites in Central America: contributions to agroecological transition and implications for educators - Conz, Brian W. (2018)
Central America has been an important region for the agroecological revolution, building on a history of intensive smallholder farming practices, farmer-to-farmer knowledge sharing and agrarian social movements.  Permaculture is an approach to ecological site design and agroecological transition, which has grown in popularity in Central America in recent years.  Permaculture’s entrance into the larger movement for agroecology in Central America raises some important questions.  How does permaculture intersect with these existing forces?  How can permaculturalists address perceptions that it is yet another colonialist development intervention by well-meaning Northerners?  What are the implications for educators who visit permaculture demonstration sites with students?  In order to explore these questions and to contribute to discussions regarding permaculture’s contribution to agroecological transition in Central America I visited two permaculture demonstration sites and participated in site tours.  I discussed site features with farmers and gathered information from farm websites.  I bring these experiences into conversation with the academic literature on agroecology and permaculture.  I conclude that permaculture sites make valuable contributions to agroecological transition in Central America.  I also identify important risks that sustainability educators using permaculture demonstrations sites should be aware of and I offer suggestions for addressing these risks.